Parental Authority, Adolescent Defiance, and Risk-Taking: Predictors of Unintentional Injuries in Israeli Youth. - Godler, Yigal; Calif, Elad; Agam, Aviad (Journal of Child & Family Studies, 2025)
This study explores the role of parental authority and adolescent defiance in shaping risk-taking behaviors and unintentional injuries among Israeli youth. We surveyed adolescents aged 15–17 (n = 501), to examine the association between adolescent conformity to parental expectations, self-reported risk behaviors, and injury experiences. Results revealed that adolescents who prioritized fulfilling parental expectations were less likely to report injuries, while those perceiving themselves as more cautious than their parents were less likely to experience near-injury incidents within their social circles. Surprisingly, adolescents who reported frequent conflicts with their parents were also less likely to sustain injuries, suggesting that such interactions may reflect parental involvement and adolescents' receptivity to guidance. These findings underscore the complex interplay between parental engagement, adolescent defiance, and risk behavior, highlighting the protective potential of parental influence within the family context. Highlights: Adolescents' conformity to parental expectations is linked to a lower likelihood of self-reported injuries. Perceiving oneself as more cautious than parents reduces the probability of near-injury incidents in social circles. Parental conflicts may reflect engagement and reduce adolescents' risk-taking. Defiance of parental authority is associated with increased risk-taking behavior and injury likelihood. Findings emphasize the role of parental involvement in mitigating adolescent risk behaviors and unintentional injuries.